O poder nos muros do silêncio: abuso sexual, segredo e família - Rondon, Elizabeth da Silva Alcoforado (2016)
The objective of this work was to analyze how the silence pact is constituted as a power device in cases of intrafamily sexual abuse, generating a social shame as an individual emotion of social repercussion. It was assumed that sexual abuse removes the family from its equilibrium aura, showing a fracture in the internal context, caused by two elements: incest and silence. Thus, we sought to understand the triangulation between the structuring elements of recurrent intrafamily sexual abuse: incest; the silence / secret and the break of these. It was based methodologically by a qualitative approach, and a structured interview was used as a data collection instrument, applied among professionals working in the protection / assistance to the victims, in the scope of health and social assistance, and among some victims participating in the research. Studies of Psychology, Anthropology and Sociology based the phenomenon comprehhension and its analysis theoretically, through the reading of different authors such as Boltanski (2012), Simmel (2009, 2011 and 2013), Veena Das (1999; Pollak (1989), Scheff (2016) and Foucault (1999). The research pointed to the understanding of sexual abuse as a social phenomenon that aggregates structuring elements like power, in the domestic spaces. In this sense, the mediation of professionals working in social and health assistence is necessary to break the silence pact. We hope to promote a broader reflection on the training and intervention practices of these professionals, starting from the understanding of the categories secrecy and silence, clarifying victims and relatives that this phenomenon represents a public health issue, demanding serious state interventions.